2018
DOI: 10.1016/j.jaad.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fezakinumab (an IL-22 monoclonal antibody) in adults with moderate-to-severe atopic dermatitis inadequately controlled by conventional treatments: A randomized, double-blind, phase 2a trial

Abstract: Fezakinumab was well-tolerated, with sustained clinical improvements after last drug dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
201
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(210 citation statements)
references
References 30 publications
3
201
0
6
Order By: Relevance
“…Our results suggested that FAM13A is a positive regulator of IL-22 production by memory CD4 + T cells and thus females with higher expression of FAM13A are likely to have more pronounced IL-22 responses in vivo . IL-22 acts on epithelial cells to promote the release of anti-microbial peptides and chemokines as well as wound healing and regenerative gene programs, and thus plays an important role in barrier immunity as well as in promoting excessive inflammatory responses in skin diseases, where IL-22 blocking therapies have shown success (Guttman-Yassky et al, 2018). Recent studies have found that serum and sputum IL22 levels were elevated in patients with COPD (Zhang et al, 2013), implying IL-22 may also have a pathogenic role in COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggested that FAM13A is a positive regulator of IL-22 production by memory CD4 + T cells and thus females with higher expression of FAM13A are likely to have more pronounced IL-22 responses in vivo . IL-22 acts on epithelial cells to promote the release of anti-microbial peptides and chemokines as well as wound healing and regenerative gene programs, and thus plays an important role in barrier immunity as well as in promoting excessive inflammatory responses in skin diseases, where IL-22 blocking therapies have shown success (Guttman-Yassky et al, 2018). Recent studies have found that serum and sputum IL22 levels were elevated in patients with COPD (Zhang et al, 2013), implying IL-22 may also have a pathogenic role in COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Recent published phase 2 studies have demonstrated that the monoclonal antibodies that block IL-13 (lebrikizu­mab and tralokinumab) are effective in patients with moderate to severe AD [150, 151]. By applying fezakinumab, an anti-IL-22 antibody, a significant decline in disease severity scores (SCORAD, affected body surface area, and investigator global assessment), could be achieved and a pathogenic role for IL-22 in AD could be demonstrated [152]. Notably, therapy with ustekinumab that inhibits the common p40 subunit of IL-12/IL-23 and thus the production of IL-17, IL-21, and IL-22, was not effective in patients with moderate to very severe AD [153, 154].…”
Section: Therapeutic Management Of Admentioning
confidence: 99%
“…Fezakinumab, an IL-22 monoclonal antibody, showed efficacy only for severe AD (SCORAD ≥50) in a phase 2 clinical trial. 113 Another report suggested that fezakinumab may be more effected for patients with high baseline IL-22 expression. 114 Interestingly, selective targeting of some propruritogenic factors such as TSLP has shown mixed results in clinical testing.…”
Section: Biologic Agentsmentioning
confidence: 99%